Commentary: The Emerging Law of Federal Assistance - Richard B. Cappalli (Washington University Law Quarterly, 1982)
The Supreme Court offers procedural due process to statutory entitlements, and the grant-in-aid qualifies as such an entitlement.
Keywords: Administrative procedure; Due process of law; Grants-in-aid; United States